Mass Communication Is More Than A One-Way Street: On the Persistent Function and Relevance of Journalism - Fürst, Silke; Schönhagen, Philomen; Bosshart, Stefan (Javnost-The Public, 2015)
In contrast to traditional mass communication, online communication is conceived as interactive and more participatory. Due to new technological possibilities and cultural changes, the audience is said to now play a crucial role in public discourse. Many scholars argue that journalists have lost their gatekeeping role and should strengthen user participation by giving voice to individual citizens. Yet research has shown that user participation accounts for only a small part of everyday media practices. Moreover, the visibility of ordinary citizens in media coverage is still low. This paper offers an explanation for these findings and sets out to rethink the structure and processes of mass communication as well as the ways in which users are participating in public discourse. Drawing on a discursive approach developed in early communication research, we highlight the genuine interactive nature of mass communication. Interactivity in this sense is not realised by the expression of every single individual, but by the exchange of statements between the representatives of diverse groups in society. Representation is crucial for journalism to fulfil its core function of providing a concentrated but comprehensive overview of the ongoing social discourse. The article concludes by discussing research needs and future challenges of journalism.